2018
DOI: 10.1186/s12935-018-0638-4
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA ROR promotes breast cancer by regulating the TGF-β pathway

Abstract: BackgroundBreast cancer is the leading cause of oncological mortality among women. Efficient detection of cancer cells in an early stage and potent therapeutic agents targeting metastatic tumors are highly needed to improve survival rates. Emerging evidence indicates that lncRNAs (long noncoding RNAs) are critical regulators of fundamental cellular processes in a variety of tumors including breast cancer. The functional details of these regulatory elements, however, remain largely unexplored.MethodsIn this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 23 publications
1
43
0
Order By: Relevance
“…The lncRNA ROR has been first described in iPSCs and have shown to have a role in embryonic stem cells generation [10]. In the field of BC, Hou et al firstly reported that ROR could induce epithelial-to-mesenchymal transition and contribute to BC tumorigenesis and metastasis [19], and ROR could promote BC by regulating the TGF-β pathway [20]. ROR and miR-145 were elaborated to regulate invasion in triple-negative BC via targeting ARF6 [11].…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNA ROR has been first described in iPSCs and have shown to have a role in embryonic stem cells generation [10]. In the field of BC, Hou et al firstly reported that ROR could induce epithelial-to-mesenchymal transition and contribute to BC tumorigenesis and metastasis [19], and ROR could promote BC by regulating the TGF-β pathway [20]. ROR and miR-145 were elaborated to regulate invasion in triple-negative BC via targeting ARF6 [11].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the wound-healing assay showed that overexpression of linc-ROR increased BC cells (MCF10A) mobility. Transwell assay revealed that linc-ROR overexpression remarkably increased the migration ability (Hou et al, 2018). More importantly, they found that ectopic expression of linc-ROR induced an EMT program in MCF10A cells.…”
Section: Breast Cancermentioning
confidence: 97%
“…Hou et al investigated the expression level of linc-ROR in 94 patients (Hou et al, 2018). Their results revealed that the level of linc-ROR was increased in BC tissues.…”
Section: Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…As a ceRNA of mir-145, ROR functions via loss of mature miR-141 expression leading to the protection of pluripotency factors [213]. In BC cells and in patient samples, lncRNA ROR was not only linked to the self-renewal of stem cells, EMT transition, and drug resistance but also to poor prognosis indicating its significance in tumorigenesis process [215][216][217][218][219][220]. Mainly, lnc-ROR functions via targeting of ZEB1/2 and TGF-β signaling leading to modulation of EMT markers such as vimentin and neural (N)-cadherin and induction of EMT process [218,219,221,222].…”
Section: Role Of Micrornas and Lncrna In Bcscsmentioning
confidence: 99%